HOMESCHOOLING AS A STUDY STRATEGY IN TIMES OF COVID-19 - Shirley Tanya Basurto Mendoza; Lubis Carmita Zambrano Montes (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research emphasized homeschooling as a strategy to teach in times of Covid19, it deals with the role that parents play when they take responsibility for the education of their children in the home, where they form an unrivaled connection of trust, respect, and discipline, as well as enjoyable experiences by reinventing teaching from their perspective. The methodology used was inclined towards qualitative-bibliographic research that supported the inquiry gathered through information gathered from recommended sources and the vast research proposed by his mentor John Holt, in books, magazines and interviews, which are a reference of this pedagogy. The testimonies of the families are relevant to the investigation, an invaluable contribution was obtained from them. The nexus of education and home was approached by Holt, but without a doubt what he defended the most was his thesis Unschooling or without education, since for him it would correspond to children to learn naturally, immersed in the discoveries that are achieved by existing, that learning becomes a talk where confidence, discernment and motivation prevail. The objective of this study was to demonstrate that natural family learning serves as a tactic for learning in Covid19. It is concluded that homeschooling is an alternative to training children. Fully confident youth study the activities of daily living and examine the unknown, supplemented by the expertise of some individualized entertainment in the arts or sports.